Modelling and Simulation of Field-Oriented Control of Permanent Magnet Synchronous Motor - Tripathi, Hari; Marahatta, Kushal; Gupta, Bikash Kumar; Yadav, Nabin Kumar; Shrestha, Suraj (Journal of Engineering and Sciences, 2023)
A permanent Magnet Synchronous Motor is an electric motor driven by permanent magnets, finding widespread use in industrial and robotic applications due to their high efficiency, low inertia and high torque to volume ratio. Various control techniques have been implemented to make drive systems control more precise and efficient. This paper presents a Field Oriented Control (FOC) as a novel method to effectively control motor torque and speed. The primary objective of this research is to develop a detailed model of FOC-PMSM and simulate its dynamic behaviour under various operating conditions. The system is simulated in MATLAB/Simulink to check the validity, reasonability and expected outcomes. Simulation results show that the designed control system can track speed and current references with minimum error. PMSM depicts better dynamic performances with FOC implementation.